Molecular Genetic Testing of Stability and Identification of Vnukovo-32 Strain Used for Production of the Cultural Concentrated Purified Inactivated Dry Rabies Vaccine - G. M. Ignatyev; A. S. Oksanich; L. P. Antonova; T. G. Samartseva; S. V. Mosolova; K. M. Mefed; l. V. Gmyl; N. A. Netesova (Биопрепараты: Профилактика, диагностика, лечение, 2020)
Rabies is an acute viral disease caused by a virus of the Rhabdoviridae family of the Lyssavirus genus, which affects the central nervous system and is characterised by absolute mortality. Vaccination is the only way to prevent the disease in humans. One of the products used for vaccination is a cultural concentrated purified inactivated dry rabies vaccine produced by the Federal State Budgetary Institution of Science “Chumakov Federal Scientific Center for Research and Development of Immune-and-Biological Products of Russian Academy of Sciences” (hereinafter—Chumakov Center).The aim of the study was to examine the structure of the working virus seed of Vnukovo-32 strain used by the Chumakov Center for rabies vaccine production, to assess its genetic stability during production, to explore the possibility of using molecular genetic methods for identification of the production strain in the finished dosage form, and to study the nucleotide sequence of the CVS strain.Materials and methods: Vnukovo-32 rabies virus production strain, working virus seeds, finished batches of the rabies vaccine, CVS fixed rabies virus strain used in the assessment of specific immunity. The molecular genetic study was performed using RT-PCR followed by restriction and sequencing.Results: the paper presents the results of nucleotide sequence analysis of the G gene fragment obtained from the Vnukovo-32 production strain, batches of the working virus seed, and finished batches of the rabies vaccine produced in 2012, 2018, and 2019, and the CVS fixed rabies virus strain used in the assessment of the vaccine’s specific immunity. The study demonstrated that restriction analysis could be used for Vnukovo-32 strain identification at all production stages, including the finished dosage form.Conclusion: Vnukovo-32 and CVS strains used by the Chumakov Center are rabies viruses. Analysis of the nucleotide sequence of the G gene fragment showed that the Vnukovo-32 strain remains stable throughout different production stages. The obtained nucleotide sequence of gene G of the Vnukovo-32 strain was deposited in GenBank (accession number MN116503). The study demonstrated that restriction analysis could be used for Vnukovo-32 strain identification at all production stages, including the finished dosage form.